The Dynamics of European Inflation Expectations - Jonas Dovern; Joerg Doepke; Ulrich Fritsche; Jirka Slacalek (Hamburg University, Department Economics and Politics, 2006)
We investigate the relevance of the Carrolls sticky information model of inflation expectations for four major European economies (France, Germany, Italy and the United Kingdom). Using survey data on household and expert inflation expectations we argue that the model adequately captures the dynamics of household inflation expectations. We estimate two alternative parametrizations of the sticky information model which differ in the stationarity assumptions about the underlying series. Our baseline stationary estimation suggests that the average frequency of information updating for the European households is roughly once in 18 months. The vector error-correction model implies households update information about once a year.
Keywords: D84; E31; 330; Inflation expectations; sticky information; inflation persistence